Treatment of Gunshot-Related Mandibular Fracture with Splint-Guided Reduction: Case Report - Kaya Demet; Konaş Ersoy; Kocadereli İlken; Mavili Mehmet Emin (Balkan Journal of Dental Medicine, 2021)
Background/Aim: Gunshot injury-related mandibular fractures often have a complex pattern, characterized by comminution, bone loss, and soft-tissue avulsion. The management is difficult and varies between individual cases.